Advanced further training or dual higher education study: a choice experiment on the influence of employers' preferences on career advancement - Tobias Maier (Journal for Labour Market Research, 2022)
Although the number of graduates with a bachelor's degree has risen over recent years, little information is available as to which position such persons hold within an establishment and whether they compete on the career ladder with persons from the vocational sector with advanced further training, for example master craftsmen, technicians or certified senior clerks. This article presents the results of a choice experiment in which decision makers at German establishments had to choose between three candidates to fill a vacant project management position. The candidates had completed either advanced further training or a bachelor's programme in dual courses of study (training- or practice-integrated). They further differed in other characteristics, such as the place of training, final mark, occupational experience and specialisation. The results show that the training strategy of the establishments as well as their general experience with bachelor's graduates plays an important role when the chances of career advancement are assessed. Persons with advanced further training certificates are only preferred if the establishments exclusively support advanced training programmes. For all other establishments the qualification path of the candidates does not matter. The results give rise to the supposition that dual higher education studies will represent an attractive alternative for young people as opposed to advanced further training if such dual programmes are expanded and awareness of them increases.
Keywords: C12; C25; C51; C88; C91; D22; D46; D83; I21; I23; J24; 330; Advanced further training; Bachelor's; Choice experiment; Dual study programmes; Establishment survey; Germany; Higher education; Vignette study